2005
DOI: 10.1002/0471142956.cy0622s33
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Screening for the HLA‐B27 Antigen on Peripheral Blood Lymphocytes

Abstract: HLA‐B27 is common to the entire group of seronegative spondyloarthropathies, and assessment of HLA‐B27 is of diagnostic importance if any of these diseases are considered. Among the alternatives to traditional typing by the complement‐dependent cytotoxicity assay, flow cytometric HLA‐B27 screening is most widely used in general diagnostic laboratories, as it is simple, rapid, and cost effective. This unit describes screening for HLA‐B27 on peripheral blood lymphocytes using more than one HLA‐B27 monoclonal ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…Notably, mAb 3E12 cross-reactivity on HLA-A2 can be blocked by the addition of anti-HLA-A2-specific mAb clone BB7.2 (results not shown). Interestingly, similar observation was made with a commercial anti-HLA-B27 mAb (clone GS145.2), whose cross-reactivity on HLA-B17, -B37 and -B47 specificities is blocked by the addition of mAb clone FD705 (23,24).…”
Section: Direct If Staining Of Whole Blood Samplessupporting
confidence: 72%
“…Notably, mAb 3E12 cross-reactivity on HLA-A2 can be blocked by the addition of anti-HLA-A2-specific mAb clone BB7.2 (results not shown). Interestingly, similar observation was made with a commercial anti-HLA-B27 mAb (clone GS145.2), whose cross-reactivity on HLA-B17, -B37 and -B47 specificities is blocked by the addition of mAb clone FD705 (23,24).…”
Section: Direct If Staining Of Whole Blood Samplessupporting
confidence: 72%
“…The photomultiplier tube voltage was adjusted daily to maintain a constant analysis window using FACSComp software with CaliBRITE beads and HLA‐B27 beads (4, 5). For this study, two different GS145.2‐conjugated antibody lot numbers were used.…”
Section: Methodsmentioning
confidence: 99%
“…The photomultiplier tube window was adjusted daily to maintain a constant analysis window using FACSComp software with CaliBRITE beads (4, 5).…”
Section: Methodsmentioning
confidence: 99%
“…For flow cytometry of the parameters HLA-B27, CD-45 and CD-34 + lymphocytes, studies were performed and showed inter-laboratory variation [38,[71][72][73][74]. The competition with PCR methodology hampered further efforts.…”
Section: Hemocytometry and Flow Cytometrymentioning
confidence: 99%